Kemampuan Bina Diri Anak dengan Gangguan Spektrum Autisme Ditinjau dari Pengetahuan dan Penerimaan Orangtua - Johan Prabawa; Endang Widyorini; Emiliana Primastuti (Humanitas (Jurnal Psikologi), 2022)
The study aim to analyze the relationship between parental knowledge about autism and parental acceptance of children with ASD on the DLS in children with ASD. The statistical technique used was a correlation with 15 parents who have ASD children with an age range from 8 to 18 years, consisting of 10 boys and 5 girls. The sampling technique used was purposive sampling with a scale instrument and the data analysis technique used Spearman’s rho. Based on the result of this research, it was found that the significance value of the p value of parental acceptance in children with ASD Sig. (1-tailed) with a significant correlation coefficient p = .027 (< 0.05) so it can be concluded that there is a significant relationship between parental acceptance in children with ASD and DLS in children with ASD.